2011
DOI: 10.1007/s12687-011-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Young smokers’ views of genetic susceptibility testing for lung cancer risk: minding unintended consequences

Abstract: Assessment of smokers’ responses to individualized feedback of genetic susceptibility has shown little or no influence on smoking cessation outcomes. One explanation is that smokers may be having unintended responses that undermine the feedback’s motivational impact (e.g., fatalism or downplaying risk). In preparation for a large randomized trial with college smokers, we conducted a qualitative pilot study to explore smokers’ motives for genetic testing and how these motives might influence interpretation of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…This finding is consistent with prior studies showing that people are more likely to avoid health information that potentially creates an undesired emotion, challenges a desired self-view or eventuates an unwanted action 30. It is noteworthy that this theme of avoidance emerged from a second purely qualitative study our research team conducted using semistructured interviews with a separate sample of undergraduates in a different part of the country 31. These findings suggest that avoidance as a motivation is particularly important in a young healthy population with numerous priorities other than health.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with prior studies showing that people are more likely to avoid health information that potentially creates an undesired emotion, challenges a desired self-view or eventuates an unwanted action 30. It is noteworthy that this theme of avoidance emerged from a second purely qualitative study our research team conducted using semistructured interviews with a separate sample of undergraduates in a different part of the country 31. These findings suggest that avoidance as a motivation is particularly important in a young healthy population with numerous priorities other than health.…”
Section: Discussionsupporting
confidence: 89%
“…Results of one qualita tive study illustrate misconceptions that can result from such dual thinking (Docherty et al, 2011). Young adult smokers believed that genetic susceptibility testing for lung cancer was irrelevant because they believed they would quit smoking before they suffered any harms from smoking (Docherty et al, 2011;van Oostrom et al, 2007). Clearly, these young smokers did not understand that genetic sus ceptibility lessens tolerance to tobacco smoke exposure even with shortened exposure.…”
Section: Om M U N Icatio N S a B O U T G E N E -E N V Iro N M E N Tmentioning
confidence: 99%
“…Interest in and uptake of novel forms of genetic susceptibility feedback testing, examined largely through research, remains variable, and has been shown to be moderated by a number of demographic, psychological, and psychosocial factors [6-8,11,12]. Little is currently known about how patients will react to a genetic susceptibility feedback test that examines a combination of genetic and environmental (for example, dietary) risk factors, and whether such a combination test might prove to be a superior stimulus for health behavior change compared to a genetic susceptibility feedback test alone.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature examining SNP-based genetic susceptibility feedback testing provides additional insight into reasons why individuals may or may not pursue genetic testing presented in a different context. For example, like patients seeking a predictive genetic testing for cancer risk (for example, BRCA1/2 ), individuals with elevated objective or perceived risk of adult disease may seek genetic susceptibility feedback due to increased perceived relevance of the testing to their health [6,7,9,12,15], increased cancer worry [6,8], or to support an already elevated perceived risk of developing cancer or motivation to change behavior, even when testing for a low penetrance risk gene [6,8,16]. These same high-risk individuals may also express strong intentions to modify behaviors dependent on further information about risk [7,8,11,15], but may ultimately fail to move forward with testing due to practical (for example, access) and psychological barriers (for example, low motivation or awareness) [11].…”
Section: Introductionmentioning
confidence: 99%